The Eighth ECS Workshop on "Calcium Signaling in Aging and Neurodegenerative Diseases" - Parys, Jan B. (2019)
The European Calcium Society (ECS) is very glad to present the realization of a special issue of the International Journal of Molecular Sciences (IJMS) related to the eighth ECS workshop organized this year around the theme of "Calcium Signaling in Aging and Neurodegenerative Diseases" [...].